EP349/#554 Logistics of time required to implement a screen-and-treat strategy using point-of-care HPV testing for the prevention of cervical cancer. (4th December 2022) - Mbatani, Nomonde; Saidu, Rakiya; Castor, Delivette; Boa, Rosalind; Moodley, Jennifer; Kuhn, Louise; Denny, Lynette
Abstract : Objectives: We conducted a time-motion study to assess implementation feasibility of POC HPV testing within a SAT program. Methods: We recruited women from a primary health care facility in Khayelitsha, Cape Town between February 2015-May 2016. We identified the following critical steps necessary if POC HPV testing is to be integrated into a SAT protocol: consent, history and examination, and sample testing on-site. Since HPV Xpert was used, which requires 60 minute run time, we estimated that the total visit time until a treatment decision could be made, assuming no delays, would be 95 minutes. If treatment is indicated, an additional 30 minutes would be needed to complete the visit Results: We enrolled 715 women, 223 (31.2%) were HPV-positive. Women were aged 42.7 (SD 8.6) years on average. Median visit time until a treatment decision could be made was 2.93 hours (range: 0.58–6.73; IQR 1.38) overall, 3.13 hours (range: 1.71–6.73; IQR 1.23) for participants who stayed to receive their HPV results and 1.97 hours (range: 0.58–5.00; IQR 1.64) for those who did not (figure 1). The decision to stay for receipt of HPV results was associated with earlier arrival in the day ( table 1 ). Conclusions: Staying to receive results adds almost an hour to the visit, but it enables treatment at the same visit as screening. Patients who arrived later in the day were less likely to stay for their results. The logistics of POC testing are complex and require careful consideration to ensure efficient visits with as little wait-times for patients as possible.